Accessory Axillary Breast Management: Is Primary Skin Excision Necessary? - Neha Chauhan (Indian Journal of Plastic Surgery)
Axillary breasts are a common entity with a reported incidence of 2 to 6% in women and 1 to 3% in men. They are more common amongst Asians than Caucasians, namely amongst South East Asians and Indians, with the highest incidence amongst Japanese. While modalities like CoolScupting™, Kybella™ injections, and BodyTite™ have been used by surgeons for management of axillary breasts, the most effective treatment for this condition remains surgical management involving a combination of liposuction of the axillary breast with excision of the gland and skin. In the author's experience, primary skin excision always leaves a long visible scar that widens over time, at times leading to contractures and restricted axillary movements even when closure looks tension free on the table. Any skin excess is best dealt with secondarily. The author uses a modified protocol without any primary skin excision in axillary breast management to achieve excellent results with minimal scars.